2014
DOI: 10.1002/ffj.3202
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and odour properties of the four stereoisomers of 2‐hexyl‐4‐acetoxytetrahydrofuran

Abstract: The four stereoisomers of 2-hexyl-4-acetoxytetrahydrofuran were prepared starting from (R)-or (S)-1-decen-4-ol (>96% ee). They were obtained by kinetic resolution of racemic homoallylic alcohol catalysed by Novozym 435 (Candida antarctica). (R)-or (S)-1-Decen-4-ol proceeded Sharpless asymmetric dihydroxylation (AD) using AD-mix-α or β as an oxidant followed by ring closure to afford cis-2-hexyl-4-hydroxytetrahydrofuran as the major product with 50-60% de. The diastereomers were separated by derivatization to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As an example, they synthesized both enantiomers of a new odorant 1 on the basis of the structure of Cashmeran, a polycyclic musk, and found that the ( R )‐enantiomer ( R )‐ 1 displayed a typical woody–musky Cashmeran odour, and the ( S )‐enantiomer ( S )‐ 1 had no musk odour (Figure ) . Enantiomers of many chemical compounds are perceived differently as odorants . Only ( R )‐ 1 was similar in odour profiles to Cashmeran in spite of the structure of 1 being different from that of Cashmeran.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, they synthesized both enantiomers of a new odorant 1 on the basis of the structure of Cashmeran, a polycyclic musk, and found that the ( R )‐enantiomer ( R )‐ 1 displayed a typical woody–musky Cashmeran odour, and the ( S )‐enantiomer ( S )‐ 1 had no musk odour (Figure ) . Enantiomers of many chemical compounds are perceived differently as odorants . Only ( R )‐ 1 was similar in odour profiles to Cashmeran in spite of the structure of 1 being different from that of Cashmeran.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these compounds belong to the large family known as acetogenins . Moreover, compounds with a THF–diol moiety have been shown to inhibit development and reproduction in nematodes and rats. , Compounds of this class also stimulate proliferation of human breast and prostate cancer cells. ,, Finally, the four stereoisomers of 2-hexyl-4-acetoxy­tetra­hydro­furan have recently been reported to have different odor properties and intensity …”
mentioning
confidence: 99%